Coffee Economy in Late Colonial Netherlands East Indies: Estates and Capital, 1890–1940 - Dias Pradadimara (Lembaran Sejarah, 2017)
This paper provides an attempt to look at the coffee economy in late colonial Netherlands East Indies, by focusing on the private estates that produced coffee and on the capital-owning class who invested in these estates. Since mid-19th century there was an increasing accessibility for would-be planters to gain access to land, especially in Java and Sumatra. Attracted to the increasing, if volatile, the world price of the commodity, coffee-producing estates were established in great numbers across the archipelago, despite the threat of the coffee leaf rust plantdisease. Only the attraction to rubber planting and the economic crisis in the 1930s dampened the enthusiasm. At the same time, the individual planters and Indiesbased companies who controlled most of the coffee producing estates in the late 19th century were gradually replaced by incorporated companies both based in the Indies and in the Netherlands. The increasing flow of capital following the rubber boom in the early 20th century made the role of individual planters and Indiesbased companies declined further.